Media Pop-Up Book Materi Siklus Hidup Hewan dalam Meningkatkan Prestasi Belajar Siswa Sekolah Dasar - Shahnaz Meuthia De Stanza; S Sholehuddin (Universitas Pendidikan Indonesia (UPI), 2023)
This research is motivated by the limitations of learning media used by teachers in the learning process at MI Hamka Kalibeber. The research approach used in quantitative with a Pre-Experimental model in the form of One-Group Pretest-Posttest Design. The total population in this study was 20 students and all of them were used as samples. The results of this study indicate that the use of pop-up book media in learning can be effective, this is evidenced by the N-Gain test score of 0.664 and the caculation of the effect size test of 79.62. The use of pop-up media is proven to improve learning achievement, this is evidenced by an increase in the average pre-test of 50.00 and post-test of 83.25. Thus there is an increase of 33.25. This study’s results are expected to benefit teachers, students, and further researchers.